1991
DOI: 10.1161/01.res.69.3.623
|View full text |Cite
|
Sign up to set email alerts
|

Sulfonylureas, ATP-sensitive K+ channels, and cellular K+ loss during hypoxia, ischemia, and metabolic inhibition in mammalian ventricle.

Abstract: Sulfonylurea derivatives glibenclamide and tolbutamide are selective blockers of ATP-sensitive K+ (KATP) channels. However, their ability to prevent cellular K+ loss and shortening of action potential duration during ischemia or hypoxia in the intact heart is modest compared with their efficacy at blocking KATP channels in excised membrane patches. In the isolated arterially perfused rabbit interventricular septum, the increase in unidirectional K+ efflux and shortening of action potential duration during subs… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

11
114
1
1

Year Published

1993
1993
2010
2010

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 202 publications
(127 citation statements)
references
References 41 publications
11
114
1
1
Order By: Relevance
“…Another explanation may be that the sarcK ATP channel current activated by metabolic stress might be more resistant to amiodarone. It was demonstrated that sulfonylurea drugs such as glibenclamide and tolbutamide were no longer able to inhibit the opening of sarcK ATP channels during severe metabolic stress although the precise mechanism(s) have not been fully clarified (Venkatesh et al, 1991;Findlay, 1993). The effective concentration to inhibit the sarcK ATP channel current in this study was similar to or less than those needed to inhibit the other channels (Balser et al, 1991;Sato et al, 1994;Mori et al, 1996;Watanabe et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…Another explanation may be that the sarcK ATP channel current activated by metabolic stress might be more resistant to amiodarone. It was demonstrated that sulfonylurea drugs such as glibenclamide and tolbutamide were no longer able to inhibit the opening of sarcK ATP channels during severe metabolic stress although the precise mechanism(s) have not been fully clarified (Venkatesh et al, 1991;Findlay, 1993). The effective concentration to inhibit the sarcK ATP channel current in this study was similar to or less than those needed to inhibit the other channels (Balser et al, 1991;Sato et al, 1994;Mori et al, 1996;Watanabe et al, 1996).…”
Section: Discussionmentioning
confidence: 99%
“…However, a slight variability of the metabolic state of the individual myocytes in our study could explain the variability of the blocking effects of tolbutamide at millimolar concentrations. The metabolic state of the individual myocytes seems to modulate the sulfonylurea-induced block of cardiac KATP channels, since the blocking effects of sulfonylureas on cardiac KATp channels are lost after metabolic inhibition and cardiac K A T~ channels activated by KCOs are more sensitive towards sulfonylurea-induced block when compared to channels activated by metaboIic inhibition (Venkatesh et al 1991;Findlay 1993;Krause et al 1995).…”
Section: Discussionmentioning
confidence: 99%
“…18 Pharmacological agents that increase K ATP channel conductance 9,19 have effects similar to those of ischemia on action potentials and are also arrhythmogenic. 14,16,20,21 The focus on the arrhythmogenic role of K ATP channel activation has been during acute ischemia. 4,14,17 During this period, epicardial muscle that eventually forms the EBZ undergoes more severe electrophysiological alterations than endocardial muscle, 22,23 partly related to greater activation of the K ATP channels.…”
Section: Role Of K Atp Channels In Ischemic Arrhythmiasmentioning
confidence: 99%
“…14,16,20,21 The focus on the arrhythmogenic role of K ATP channel activation has been during acute ischemia. 4,14,17 During this period, epicardial muscle that eventually forms the EBZ undergoes more severe electrophysiological alterations than endocardial muscle, 22,23 partly related to greater activation of the K ATP channels. 24 During subsequent days, muscle cells in the EBZ undergo changes in ion channels that control repolarization, resting membrane potential, and depolarization and are related to changes in ion channel protein synthesis.…”
Section: Role Of K Atp Channels In Ischemic Arrhythmiasmentioning
confidence: 99%